Fabrication of EP@PDMS@F-SiO2 Superhydrophobic Composite Coating on Titanium Alloy Substrate - Chaoming Huang; Jinhe Qi; Jie Li; Xinchi Li; Jiawei Chen; Shuo Fu; Yanning Lu (Biomimetics)
In this study, a preparation method of superhydrophobic composite coating based on a titanium alloy (Ti-6Al-4V) substrate is proposed. The micro-scale pit array structure was fabricated via laser etching technology. Utilizing the synergistic effects of epoxy resin (EP), polydimethylsiloxane (PDMS), and fluorinated nanosilica (F-SiO2), we successfully prepared an EP@PDMS@F-SiO2 composite coating. The effects of the contents of EP, PDMS, and F-SiO2 on the surface wettability, mechanical stability, and UV durability were studied by optimizing the coating ratio through orthogonal experiments. The results show that the micro–nano composite structure formed by laser etching can effectively fix the coating particles and provide excellent superhydrophobicity on the surface. The coating retains high hydrophobicity after paper abrasion (1000 cm under a 200 g load), demonstrating the mechanical stability of the armor-like structure, High-content F-SiO2 coatings exhibit greater UV durability. In addition, the coating surface has low droplet adhesion and self-cleaning capabilities for efficient contaminant removal. The research provides theoretical and technical support for the design and engineering application of a non-fluorinated, environmentally friendly superhydrophobic coating.